Izgrajevanje tržne pozicije na mednarodnih trgih kot dimenzija učinkovite strateške zasnove mednarodnega marketinga - Jurše, Milan (Akademija MM, 1998)
In paper the systematic market position of a company in international markets is discussed. On the basis of the analysis of marketing problems of Slovenian companies in the transition process and recent developments in international business environment the paper outlines a strategic management concept of market position in international markets. First, the processes of strategic analysis is discused, followed by the examination of planning process of market position development in new target markets, the market position extension and strengthening in present markets. This process is outlined as part of the international strategic marketing management process, therefore the concept of strategic control of market position in international markets is added.
Keywords: mednarodni ekonomski odnosi; mednarodni marketing; mednarodno trženje; strategija trženja; trženje; zunanja tržišča